Turner syndrome. Our experience in develop the institutional registry and the multidisciplinary unit at italian hospital of buenos aires: A first step to the best women health follow-up - Santangelo, Liliana A; Ortiz, María Inés; Paissan, Andrea L.; Fainstein Day, Patricia; Knoblovits, Pablo (Revista del Hospital Italiano de Buenos Aires, 2019)
Turner syndrome (TS) results from the complete or partial absence of the second sex chromosome in female phenotypes. It has an incidence of 1: 2000-2500 girls born alive. Only in the last decade has been paid attention to the health of adults women with TS. Mortality is 3 times higher than in the general population due to the risk of aortic dissection cause to structural cardiovascular anomalies and atherosclerosis related to hypertension, diabetes, dyslipidemia and obesity. They also have a high prevalence of autoimmune diseases. Until nowadays in Argentina do not exist a national registry of this disease that complies with the international follow-up recommendations for these patients. We proposed to develop the institutional register at 2014 and a multidisciplinary team was created to care and follow up girls and women with TS during 2015. It was indexed to Italian Hospital of Buenos Aires’ Rare Diseases Program since 2017. After the creation of the institutional registry and the multidisciplinary team we obtained a significant improvement in cardiology, endocrinology and otorhinolaryngology schedule visits, in lipids and hydrocarbon metabolism, liver, thyroid and celiac diseases biochemical controls and in the performance of cardiovascular MNR and bone densitometry. In conclusion, the systematized and institutional follow-up, through the registry and the creation of the Interdisciplinary Unit of Turner Syndrome, allowed us to find the flaws of the care system and to optimize the follow up of this population
Keywords: Turner syndrome; Institutional Registry; multidisciplinary clinics; adult women